Culturally Restorative Child Welfare Practice - A Special Emphasis on Cultural Attachment Theory - Simard, Estelle (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
A research project was implemented through the use of qualitative secondary data analysis to describe a theory of culturally restorative child welfare practice with the application of cultural attachment theory. The research documented 20 years of service practice that promoted Anisinaabe cultural identity and cultural attachment strategies, by fostering the natural cultural resiliencies that exist within the Anishaabe nation. The research brings a suggested methodology to child welfare services for First Nation children the greater the application of cultural attachment strategies the greater the response to cultural restoration processes within a First Nation community.